A Review of Research on Extreme Heat Events in China - Ren, Weiwei (International Journal of Social Sciences and Public Administration, 2025)
Based on the current research literature on extreme high temperature events in China, this paper reviews the spatial and temporal characteristics of extreme high temperature events, causes of extreme high temperature events, identification methods of extreme high temperature events, and impacts of extreme high temperature events in China, and points out the problems existing in the research on extreme high temperature events in China.